2012
DOI: 10.4238/2012.may.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Differential expression analysis of porcine MDH1, MDH2 and ME1 genes in adipose tissues

Abstract: ABSTRACT. Malate dehydrogenases 1 and 2 (MDH1 and MDH2), and malic enzyme 1 (ME1) play important roles in the Krebs cycle for energy metabolism. The mRNA abundance changes of MDH1, MDH2 and ME1 genes were measured across six different adipose tissues from the leaner Landrace and fatty Rongchang pig breeds using quantitative real-time PCR. The mRNA of MDH1, MDH2 and ME1 was more abundant in fatty Rongchang pigs than in leaner Landrace pigs. In both breeds, females exhibited higher adipocyte volume and mRNA abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…Other metabolically important genes -ACACA and SREBF1also displayed comparably higher transcript levels in subcutaneous tissue, and the PL pigs showed an increased ACACA transcript level in the subcutaneous tissue and lower in the longissimus muscle when compared to the other breeds (PLW, Duroc and Pietrain) (Stachowiak et al 2013). Our results also confirm the data reported by Zhou et al (2012) who observed an increased ME1 transcript level in the adipose tissue of a local Chinese fatty pig breed (Rongchang) when compared with the leaner Landrace pigs. It must be noted, however, that it was not the PL breed but rather the Pietrain gilts (N = 12), which were phenotypically different from the other breeds with respect to most production traits (average backfat thickness p < 9.0 9 10 À5 , abdominal fat weight p = 3.4 9 10 À7 , lean meat content p = 5.6 9 10 À14 , daily gain p < 6.0 9 10 À4 ) except intramuscular fat content.…”
Section: Me1 Transcript Levelsupporting
confidence: 90%
“…Other metabolically important genes -ACACA and SREBF1also displayed comparably higher transcript levels in subcutaneous tissue, and the PL pigs showed an increased ACACA transcript level in the subcutaneous tissue and lower in the longissimus muscle when compared to the other breeds (PLW, Duroc and Pietrain) (Stachowiak et al 2013). Our results also confirm the data reported by Zhou et al (2012) who observed an increased ME1 transcript level in the adipose tissue of a local Chinese fatty pig breed (Rongchang) when compared with the leaner Landrace pigs. It must be noted, however, that it was not the PL breed but rather the Pietrain gilts (N = 12), which were phenotypically different from the other breeds with respect to most production traits (average backfat thickness p < 9.0 9 10 À5 , abdominal fat weight p = 3.4 9 10 À7 , lean meat content p = 5.6 9 10 À14 , daily gain p < 6.0 9 10 À4 ) except intramuscular fat content.…”
Section: Me1 Transcript Levelsupporting
confidence: 90%
“…Rongchang pig is a representative obese type of indigenous breed. In previous study, researchers seemed to be more interested in adipose tissue of Rongchang pig such as the expression level of some genes, gene polymorphism and so on (Jiang, Hua, et al, ; Zhou, Li, Li, Guan, & Li, ), while some studies on gene expression profiling of skeletal muscle (Fang, Yin, Li, Zhang, & Watford, ; Zhang, et al, ). However, information available on the expression profiling of miRNAs during myogenesis of Rongchang pig is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The present results revealed that the cytosolic (Mdh-1 and ME-1) were the only expressed isoenzymes in most samples of racing camel while both cytosolic and mitochondrial isoforms were expressed in production breed. The two essential malate dehydrogenases, Mdh-1 (cytosolic malate dehydrogenase) and Mdh-2 (mitochondrial malate dehydrogenase), play important roles in the Krebs cycle for energy production through aerobic respiration [27]. Mdh-1 and Mdh-2 are also involved in lipid synthesis by providing extramitochondrial reducing equivalents from the oxidation of malate [28,29].…”
Section: Resultsmentioning
confidence: 99%